2019
DOI: 10.2478/jee-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical characterization of Cu doped ZnO thin films deposited by RF magnetron sputtering

Abstract: Cu doped transparent ZnO thin films (CZO) were sputtered on soda lime glass substrates at three different distances between substrate and target. The effects of copper doping on the structural and optical properties were investigated by X-ray diffraction (XRD) and transmittance measurements. The XRD results indicated that CZO thin films have a preferential crystallographic orientation along the hexagonal wurtzite (002) axis. With increasing the distance between substrate-target, from 4 cm to 8 cm, the refracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Furthermore, both the normalized absorption and steady-state photoluminescence (PL) spectra of MAPbI 3 QDs in hexane with different sizes exhibited continuous tunability, as can be seen in Figure 3 b. To determine the optical band gap energy of various sizes of MAPbI 3 QDs, the dependency of ( αhv ) 2 upon the incident photons energy hv was plotted, as depicted in Figure 3 c, and the band gap ( E g ) was estimated by extrapolating the linear part of ( αhv ) 2 versus ( hv ) [ 35 ]. As shown in Table 1 , the E g of small, medium, and large MAPbI 3 QDs was 1.75 eV, 1.71 eV, and 1.67 eV, correspondingly.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, both the normalized absorption and steady-state photoluminescence (PL) spectra of MAPbI 3 QDs in hexane with different sizes exhibited continuous tunability, as can be seen in Figure 3 b. To determine the optical band gap energy of various sizes of MAPbI 3 QDs, the dependency of ( αhv ) 2 upon the incident photons energy hv was plotted, as depicted in Figure 3 c, and the band gap ( E g ) was estimated by extrapolating the linear part of ( αhv ) 2 versus ( hv ) [ 35 ]. As shown in Table 1 , the E g of small, medium, and large MAPbI 3 QDs was 1.75 eV, 1.71 eV, and 1.67 eV, correspondingly.…”
Section: Resultsmentioning
confidence: 99%
“…Following this, the absorption spectra of the samples were measured using a UV-Vis spectrometer (DR6000 model, Germany). The band gap energy of the ZnO nanoparticles was determined from the UV-visible spectra using the Tauc plot methodology [6].…”
Section: Methodsmentioning
confidence: 99%
“…[33] and Toma et.al. [34] studied structural, electrical and optical properties of ZnO/Cu/ZnO multilayer film stacking using Cu film as a sandwich layer. The results showed that ZnO/Cu/ZnO multilayer film has good crystalline properties and with an increasing Cu layer thickness, a visible light transmittance of the multilayer film is reduced, while the electrical performance improved significantly.…”
Section: Introductionmentioning
confidence: 99%